2015
DOI: 10.1002/cplu.201402366
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy‐Functionalized Basic Ionic Liquids—An Unexpected “Hydroxy” Effect on the Transesterification of Glycerides with Methanol

Abstract: New task-specific ionic liquids, hydroxy-functionalized 1methyl-3-alkylimidazolium hydroxides, were used as catalysts in the transesterification of rapeseed oil with methanol. In comparison to the well-described 1-methyl-3-butylimidazolium hydroxide [bmim]OH, the new ionic liquids show unexpectedly high catalytic activity.I nc ase of the ionicl iquid [glymim]OH, which is structurally similart og lycerol, the conversiono fr apeseed oil was nearly 100 %.Applications of ionic liquids( ILs), due to their unique pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A recent example has reported that a methylimidazolium salt with an alkyl chain mimicking the glycerol structure, promotes the almost quantitative conversion of rapeseed oils into FAMEs products [45]. …”
Section: Reviewmentioning
confidence: 99%
“…A recent example has reported that a methylimidazolium salt with an alkyl chain mimicking the glycerol structure, promotes the almost quantitative conversion of rapeseed oils into FAMEs products [45]. …”
Section: Reviewmentioning
confidence: 99%
“…[1] Functionalized and task-specific ILs are interesting as they are capable of performingaparticulara pplication. [2][3][4][5][6][7] Moreover,t he hydroxyl groups in the IL also make them useful for solubilizing inorganic salts, [2,8] synthesizingo rganic [9][10][11] and inorganic materials, [12] enzyme activity, [13,14] and so forth. [2][3][4][5][6][7] Moreover,t he hydroxyl groups in the IL also make them useful for solubilizing inorganic salts, [2,8] synthesizingo rganic [9][10][11] and inorganic materials, [12] enzyme activity, [13,14] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Moreover,t he hydroxyl groups in the IL also make them useful for solubilizing inorganic salts, [2,8] synthesizingo rganic [9][10][11] and inorganic materials, [12] enzyme activity, [13,14] and so forth. [9][10][11][12][13][14] Fewer studies are aimed at understanding the physical chemistry of these media. [14,15] Many of the above-mentioned studies are directed towards the use of hydroxyl ILs as media for the synthesis of organic and inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Bibasic sites were confirmed by two endothermic peaks on the TG-DCS curve of [Aemim]IMC. [15][16][17] 2 | EXPERIMENTAL…”
Section: Introductionmentioning
confidence: 99%